Therapist‐Aided Exposure for Women with Lifelong Vaginismus: Mediators of Treatment Outcome: A Randomized Waiting List Control Trial. (6th August 2015) - Ter Kuile, Moniek M.; Melles, Reinhilde J.; Tuijnman‐Raasveld, Charlotte C.; de Groot, Helen E.; van Lankveld, Jacques J.D.M.
Abstract Introduction Therapist‐aided exposure seems an effective treatment for lifelong vaginismus, but mechanisms of action have not yet been established. Aim The purpose of the present study was to investigate whether treatment outcome of a therapist‐aided exposure treatment was mediated by changes in positive and negative penetration beliefs or feelings of sexual disgust. Methods Participants with lifelong vaginismus were allocated at random to a 3‐month exposure (n = 35) or a waiting list control condition (n = 35). Main Outcome Measure Full intercourse was assessed daily during 12 weeks. Secondary outcome measures (complaints about vaginismus and coital pain) were assessed at baseline and after 12 weeks. Possible mediators: penetration beliefs (catastrophic pain beliefs, genital incompatibility beliefs, perceived control beliefs) and feelings of sexual disgust were assessed at baseline and 6 weeks. Results Treatment outcome (coital frequency, symptoms of vaginismus, and coital pain) at 12 weeks was mediated by changes in negative and positive penetration beliefs at 6 weeks, in particular by more pronounced reduction of catastrophic pain penetration beliefs. No evidence was found that changes in feelings of sexual disgust mediated treatment outcome. Conclusion The results strongly suggest that therapist‐aided exposure affects negative penetration beliefs and that these changes in negative penetration beliefs mediate treatment outcome in women with lifelong vaginismus. Implications for treatment are discussed. N = 4850 words. Ter Kuile MM, Melles RJ, Tuijnman‐Raasveld CC, de Groot HE, and van Lankveld JJDM. Therapist‐aided exposure for women with lifelong vaginismus: Mediators of treatment outcome: A randomized waiting list control trial. J Sex Med 2015;12:1807–1819.